2015
DOI: 10.1177/0300060515583076
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum CA125, CA19-9 and CA15-3 in endometriosis: A meta-analysis

Abstract: Aim: To evaluate the diagnostic value of serum cancer antigen (CA)125, CA19-9 and CA15-3 concentrations in endometriosis. Methods: Case-control studies evaluating CA125, CA19-9 and CA15-3 and endometriosis, published between January 2000 and November 2014 were retrieved from PubMed Õ and Google Scholar. Standardized mean differences (SMD) and 95% confidence intervals (CI) were calculated. Subgroup analyses were carried out by ethnicity and disease stage (early, stage I/II; advanced, stage III/IV). Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
4
27
0
Order By: Relevance
“…We conducted a comprehensive search strategy, robust methodology, and statistical analysis. Previously published systematic reviews, are out of date or associated with methodological bias arising from case‐control studies and verification bias arising from the reliance upon visual inspection, which is now known to be inaccurate . All studies included in this study reported the primary endpoint using the reference standard of histologically confirmed endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a comprehensive search strategy, robust methodology, and statistical analysis. Previously published systematic reviews, are out of date or associated with methodological bias arising from case‐control studies and verification bias arising from the reliance upon visual inspection, which is now known to be inaccurate . All studies included in this study reported the primary endpoint using the reference standard of histologically confirmed endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Individual studies have methodological limitations in patient selection, poor conduct of the index test, and poor conduct of the reference test . Two diagnostic reviews exist; however, the first is over 15 years old and includes studies with high risk of verification bias and the second is of poor methodological quality …”
Section: Introductionmentioning
confidence: 99%
“…The weak correlation between Ca125 and vaginal swab culture can be explained by bacterial-induced inflammation process of gynaecology organs. 14,15 This study showed that peritoneal fluid culture had significant inverse correlation with left tubal patency. This might be due to different vascularisation and pelvic anatomy, in which pathologic symptoms are also found more common in the left side.…”
Section: Discussionmentioning
confidence: 75%
“…Endometriosis is significantly associated with elevated serum CA 125 and CA 19-9 concentrations, and CA 19-9 is increased further in the more advanced stages of disease. Serum CA 125 and CA 19-9 may represent useful biomarkers for the noninvasive diagnosis of endometriosis [ 21 22 23 ]. This relation could be explained that the patients with increased risk of recurrence might accept uncritically the post-operative medical treatment for prevention [ 24 25 ].…”
Section: Discussionmentioning
confidence: 99%